Research on collaborative resource optimization technology based on convergence of computing, control and communication in Internet of vehicles - Zhilong ZHANG; Tianqi ZHANG; Xuefei LI; Danpu LIU (Dianxin kexue)
Internet of vehicles is highly dynamic and has diverse application types, including both security and non-security applications.How to satisfy differentiated requirements at the same time is one of the major challenges that Internet of vehicles face.Therefore, the convergence of computing, control and communication in Internet of vehicles was investigated, and the necessity of the collaborative management of multi-dimensional resources was outlined to improve both the driving safety and the quality of experience.Specifically, the control and communication convergence mechanism for autonomous driving, the computing and communication resource collaborative management mechanism for infotainment application, and the multi-dimensional resource collaborative management mechanism for differentiated application concurrency were introduced respectively according to the application characteristics.Finally, the technology development trend of this field was discussed based on related challenge analysis.